Sex hormones influence the intestinal microbiota composition in mice - Wu, Yi; Peng, Xinxin; Li, Xiaoya; Li, Dandan; Tan, Zhoujin; Yu, Rong (Frontiers in Microbiology, 2022)
Sex hormone secretion difference is one of the main reasons for sex dimorphism traits of animals, and also affects dimorphism of intestinal microbiota, however, their interaction is still unknown. Intestinal mucosa-associated microbiota (MAM) and intestinal luminal content microbiota (LM) belong to two different habitats according to the interaction difference between bacteria and host intestinal epithelium/nutrients. To clarify the sex dimorphism characteristics of MAM and LM and their correlation with sex hormones, twelve SPF Kunming mice from the same nest were fed separately according to gender. Eight weeks later, the samples of male intestinal mucosa (MM group), female intestinal mucosa (FM group), male intestinal contents (MC group) and female intestinal contents (FC group) were collected respectively, and then performed the next generation sequencing of 16S rRNA gene. Our results showed that the sex dimorphism of MAM was more obvious than that of LM, the relative abundance of Muribaculaceae, Turicibacter and Parasutterella in the FM group were significantly higher than those of the MM group (P < 0.001, P < 0.05, P < 0.05). Then, we measured the level of serum sex hormones in mice, and calculated the correlation coefficient between major bacteria and sex hormones. The results showed that the correlation between MAM and sex hormones was more prominent, and finally got three bacterial genera ( Muribaculaceae, Turicibacter and Parasutterella) that can best represent the relationship between sex dimorphism and sex hormones. The abundance of Parasutterella is positively correlated with estradiol and negatively correlated with testosterone, which may be related with the differences in bile acid metabolism and glucose metabolism. The decrease of Turicibacter abundance is closely related to autism. Our results shows that the abundance of Turicibacter is negatively correlated with testosterone, but positively correlated with estradiol, which can provide a hint for the prevalence of male autism. In conclusion, it is believed in our study that intestinal microbiota is probably the biological basis of physiological and pathological differences caused by gender, and intestinal MAM can better represent the sex dimorphism of mice.